Digital Transformation in Manufacturing: A Systematic Literatur Review of Performance Impacts and Strategic Gaps Analysis - Septiani, Nira; Sapitri, Intan; Rahmatsyah, Firman (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study conducts a systematic literature review (SLR) to analyze the impact of digital transformation on manufacturing performance and identify strategic gaps in current research. Ten peer-reviewed articles were selected based on relevance, methodological rigor, and thematic consistency. Key variables observed include operational efficiency, innovation, organizational readiness, and digital strategy. Data were synthesized qualitatively from studies published between 2020 and 2025. The findings reveal that digital transformation improves manufacturing performance, but its success depends on contextual factors such as leadership, digital maturity, and workforce readiness. The study highlights a lack of longitudinal research, weak integration between technology and management, and limited focus on SMEs. These findings offer strategic insights for academics and practitioners to bridge the theory-practice divide.